Testing embedded system through optimal mining technique (OMT) based on multi-input domain - J. K. R. Sastry; M. Lakshmi Prasad (Institute of Advanced Engineering and Science, 2019)
Testing embedded systems must be done carefully particularly in the significant regions of the embedded systems. Inputs from an embedded system can happen in multiple order and many relationships can exist among the input sequences. Consideration of the sequences and the relationships among the sequences is one of the most important considerations that must be tested to find the expected behavior of the embedded systems. On the other hand combinatorial approaches help determining fewer test cases that are quite enough to test the embedded systems exhaustively. In this paper, an Optimal Mining Technique that considers multi-input domain which is based on built-in combinatorial approaches has been presented. The method exploits multi-input sequences and the relationships that exist among multi-input vectors. The technique has been used for testing an embedded system that monitors and controls the temperature within the Nuclear reactors.